2010
DOI: 10.1259/dmfr/14139527
|View full text |Cite
|
Sign up to set email alerts
|

Image quality and radiation exposure in 320-row temporal bone computed tomography

Abstract: Objectives:The aim was to define image quality and radiation exposure in the recently introduced 320-row CT of the temporal bone (tb) in comparison to a 16-row tb CT. Methods: A cadaveric head phantom was used for repeated tb volume CT studies (80-120 kV, 25-150 mAs), performed in a 320-row scanner (single rotation, 0.5 mm slice thickness, kernel FC 51) in comparison to 16-row helical CT using standard acquisition parameters (SAP) of 120 kV and 75 mAs (kernel FC 53). Qualitative image evaluation was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Our results showed a SNR less pronounced in WV mode than helical, but in accordance with other studies [3,16] it is negligible . Duplicated excretory system with a urinary stone in the upper part of the lower excretory system.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed a SNR less pronounced in WV mode than helical, but in accordance with other studies [3,16] it is negligible . Duplicated excretory system with a urinary stone in the upper part of the lower excretory system.…”
Section: Discussionsupporting
confidence: 93%
“…Studies on early DSCT generations demonstrated a lesser radiation dose than MDCT, with equivalent or lesser image quality . The 3rd generation of DSCT was produced with no z ‐axis filter and novel IR technology, which promoted a statistically significant reduction in ED compared to earlier generations .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to obtain an accurate vertical incidence of the x-ray to the detection area plane of the dosimeter at the respective locations, we calculated the slant angles of the detection area plane at the respective longitudinal beam locations based on DICOM tag information and few previous reports. 1,24,25 As a result of calculation, the slant angles of the detection area plane in the RTI Piranha dosimeter were as follows: 256-row ADCT, 2.7°( ±30 mm), 5.5°(±60 mm), and 6.8°(±75 mm); 320-row ADCT, 2.9°( ±30 mm), 5.7°(±60 mm), and 7.1°(±75 mm). These values were adjusted for an accuracy within ±0.1°by using a digital clinometer.…”
Section: C2 | Beam Qualitymentioning
confidence: 99%